Medial Crural Auto-rim Flap in Primary Open Rhinoplasty - Hassan, Hazhir Najmaddin; Qadir, Ary Rahim; Hasan, Hawre Abdulsattar (Sulaimani Journal for Pure and Applied Sciences, 2022)
Background: Aging significantly affects the nasal tip and columella; thus, weakening of fibroelastic attachments in the scroll area and intercrural suspensory ligaments results in tip ptosis, separation of the medial crural footplates, and expansion of the membranous septum. Aim: Thus, we focused on a new technique to maintain tip support without grafting and treat columellar-hanging deformity by folding in the caudal edge of the medial crura as a flap instead of trimming it in patients undergoing open aesthetic rhinoplasty. Patients and Methods: In this prospective-observational study, 37 patients were enrolled between July 2020 to January 2022 at Sulaimani Plastic, Burn and Reconstructive Surgery Hospital and Royal Private Hospital in Sulaimani, Republic of Iraq. After asking the age of the patients, all participants were appropriately prepared for the surgery and underwent primary open rhinoplasty for columellar hanging deformity correction. Results: We found that all enrolled patients were satisfied with their nasal shape except one patient who complained about the columellar region's appearance but without the need for revision. Also, the objective assessment of the nasal tip support showed good maintenance upon the follow-up time for patients despite the lack of cartilage graft in the tip area. Conclusion: In the medial crural auto-rim flap technique, the excess caudal medial crural cartilage could be used as a flap instead of trimming it despite concomitant tip support intercrural augmentation and correction of the columellar hanging deformity.
Keywords: Aesthetic rhinoplasty; Prospective-observational study; Hanging columella deformity; Nasal tip support; Patient’s follow-up; Sulaimani city